THE DIAGNOSTIC YIELD OF UPPER GASTROINTESTINAL ENDOSCOPY IN PATIENTS WITH IRON DEFICIENCY ANAEMIA: Upper Gastrointestinal Endoscopy - Sajid, Muhammad Usman; Saeed, Farrukh; Ashraf, Hafiz Muhammad (Pakistan Armed Forces Medical Journal, 2008)
Objectives: The aim of this study was to determine the diagnostic yield of upper gastrointestinal endoscopy in patients with iron deficiency anaemia. Design: This was a descriptive study. Place and duration of study: The study was carried out at Military Hospital Rawalpindi from Sept 2003 to Feb 2004. Patients and Methods: Study was performed on 50 patients of iron deficiency anaemia of both sexes more than 18 years of age. Major upper gastrointestinal symptoms were asked. Esophagogastroduodenoscopy was performed on all the patients. Endoscopic biopsies of 2nd & 3rd part of duodenum were taken from the patients with insignificant endoscopic findings for histopathological examination. Results: Endoscopic examination of the upper gastrointestinal tract showed a causative lesion in 33 (66%) patients. The most common abnormality in the upper gastrointestinal tract was peptic ulceration (duodenal ulcer in 11 patients, gastric ulcer in 4). Seventeen (34%) patients with negative endoscopic studies underwent 4 to 5 duodenal biopsies. Histopathological examinations of biopsies from 2 patients were consistent with Coeliac disease. Symptoms as dyspepsia and epigastric pain were predictive of disease in the corresponding portion of the bowel. Conclusions: Upper gastrointestinal lesions are frequently found in patients with iron-deficiency anaemia particularly in patients with upper abdominal pain and dyspepsia.